Effects of Detasseling Timing and Intensity on Yield and TSS of Sweet Corn - Ghimire, Bedanta; Shrestha, Sudikshya; Kandel, Bishnu Prasad; Bhandari, Aashray; Rijal, Madan (Agronomy Journal of Nepal, 2025)
Detasseling redirects nutrients from tassel and pollen formation to ear growth that results in greater biomass accumulation, translocation, and higher carbohydrate deposition. However, limited studies exist on the right timing and intensity of detasseling. Hence, this research focused on assessing detasseling effects and identifying the optimum combination of detasseling timing and intensity for higher yield and sweetness. A two-factor randomized complete block design (RCBD) experiment was conducted in 2025 at A Plus Agro Farm, Sundarbazar, Lamjung. This experiment examined detasseling at two tassel emergence stages (50% and 100%) and three removal intensities (25%, 50%, and 75%). So, the treatment consisted of 6 detasseling combinations and one absolute control (no detasseling), replicated thrice. Observations were recorded on yield parameters and sweetness on the 81st days after sowing (DAS). All the detasseling combinations except 50:25 outperformed control. The results revealed that the interaction of timing and intensity increased sweetness (TSS) by 27% (p ≤ 0.05) and grains per cob by 24% (p ≤ 0.05) under 100:75 as compared to 50:25. The highest yield per cob (0.395 kg) was recorded under 100% tassel emergence with 75% intensity. The interaction for net plot yield per 2.1 m² was non-significant; however, 100% timing and 75% intensity increased yield by 12% (p ≤ 0.01) and 36% (p ≤ 0.001) relative to 50% timing and 25% intensity. All the measured parameters showed significant results at 75% detasseling. Overall, detasseling 75% of tassels in their full emergence showed an evident effect on yield and sweetness and can be suggested as a practical strategy for improving sweet corn productivity.